Stress, Time Pressure, Strategy Selection and Math Anxiety in Mathematics: A Review of the Literature - Caviola, Sara; Carey, Emma; Mammarella, Irene C.; Szucs, Denes (Frontiers in Psychology, 2017)
We review how stress induction, time pressure manipulations and math anxiety can interfere with or modulate selection of problem-solving strategies (henceforth “strategy selection”) in arithmetical tasks. 19 relevant articles were identified, which contain references to strategy selection and time limit (or time manipulations), with some also discussing emotional aspects in mathematical outcomes. Few of these take cognitive processes such as working memory or executive functions into consideration. We conclude that due to the sparsity of available literature our questions can only be partially answered and currently there is not much evidence of clear associations. We identify major gaps in knowledge and raise a series of open questions to guide further research.